THE OVERSIZED CARGO FORWARDING: ECONOMIC AND LEGAL ASPECTS - WORNALKIEWICZ, WLADYSLAW; KRAVCHYK, YURII; KAPLUNOVSKA, ALLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The transport of oversized cargo is becoming more and more popular, which is related to the construction of, inter alia, wind farms to generate electricity in mountain areas or on the coast of the Baltic Sea. Internet communication networks are expanding, thus requiring the construction of new relay towers. Non-divisible elements to be transported are getting longer and more difficult to be delivered and installed in the field. All this must be met by forwarding and transport of industrial long cargo. Such a situation requires specialized vehicles, monitoring and optimization of travel routes.
Keywords: oversized cargo; vehicle; semi-trailer; logistics systems; economic aspects; legal aspects